Investigating Elemental Composition and Structural Dynamics in the Planetary Nebula Ngc 7027: A Texture Analysis Approach - Belay Sitotaw Goshu (Britain International of Exact Sciences (BIoEx) Journal, 2024)
This study uses sophisticated textural and fractal studies to examine the compositional and structural properties of the planetary nebula NGC 7027 located around 3,000 light-years away in the Milky Way. Metrics like contrast, dissimilarity, homogeneity, energy, and correlation were methodically assessed across several photos using Gray-Level Co-occurrence Matrix (GLCM) texture analysis, exposing a variety of interior textures. Complex and irregular features inside the nebula are indicated by high contrast (159.064), dissimilarity (6.664), and low homogeneity (0.203) values in specific places. Fractal dimension analysis that produces values near -2 points to complex, self-similar patterns connected to evolving nebulae. Furthermore, wavelet transform analysis provides information on temperature and density fluctuations across NGC 7027 by capturing multi-scale features. Chemical composition analysis further elucidates the nebula's ionization state, with observed [N II]/Hα and [O III]/Hβ ratios of 0.55 and 2.00, respectively, aligning with standard planetary nebula profiles. These ratios imply moderate ionization and highlight the nebula’s typical elemental abundances. Radial distribution of oxygen and nitrogen further supports this compositional profile, providing evidence of nucleosynthetic processes in the progenitor star. The findings underscore a strong correlation between NGC 7027’s structural complexity and chemical composition, contributing to a deeper understanding of planetary nebula evolution. This integrative approach of texture, fractal, and chemical analyses presents a comprehensive model for studying nebular morphology and evolution.